Fatty Acids - Catala, Angel (IntechOpen, 2017)
The purpose of this book is to concentrate on recent developments on fatty acids. The articles collected in this book are contributions by invited researchers with a long-standing experience in different research areas. We hope that the material presented here is understandable to a broad audience, not only scientists but also people with general background in many different biological sciences. This volume offers you up-to-date, expert reviews of the fast-moving field of fatty acids. The book is divided into four major sections: (1) Fatty Acids in Physiopathology, (2) Fatty Acids and Cancer, (3) Fatty Acids in Aquatic Organisms, and (4) Fatty Acids in Veterinary and Dairy Products.